1991
DOI: 10.1139/f91-243
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric and Electrophoretic Approaches to Discrimination of Capelin (Mallotus villosus) Populations in the Estuary and Gulf of St. Lawrence

Abstract: The degree of differentiation between capelin (Mallotus villosus) populations in the Estuary and Gulf of St. Lawrence was evaluated using conventional and truss morphometric analyses together with electrophoretic analyses of protein-coding loci. Samples of spawning fish were collected in the same year at eight sites across NAFO divisions 4R, 4S, and 4T. While the results of conventional morphometric analyses were not conclusive, truss and electrophoretic analyses differentiated the sampled sites along an east–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 1 publication
1
18
0
Order By: Relevance
“…Such insight is a prerequisite for the formulation of criteria for units of conservation in order to reduce the risk of extinction, particularly at the intra-specific levels. The existence of significant populationlevel differences have previously been noted in estuarine fishes using both morphological and genetic criteria (Roby et al, 1991 andUiblein, 1995), providing evidence for the hypothesis of divergence due to partial isolation.…”
Section: Introductionmentioning
confidence: 76%
“…Such insight is a prerequisite for the formulation of criteria for units of conservation in order to reduce the risk of extinction, particularly at the intra-specific levels. The existence of significant populationlevel differences have previously been noted in estuarine fishes using both morphological and genetic criteria (Roby et al, 1991 andUiblein, 1995), providing evidence for the hypothesis of divergence due to partial isolation.…”
Section: Introductionmentioning
confidence: 76%
“…genetic differentiation of Barents Sea capelin from a local fjord population (Balsfjord) (Mork & Friis-Sörensen 1983) and between ocean and beach spawning capelin from Newfoundland (Dodson et al 1991). However, Roby et al (1991) showed that capelin in the St. Lawrence estuary and Gulf of St. Lawrence (eastern Canada) could be differentiated into eastern and western populations using a combination of morphometric and genetic methods.…”
Section: Introductionmentioning
confidence: 98%
“…Whereas previous studies on population genetics of capelin have used polymorphic proteins (allozymes) (Payne 1976, Mork & Friis-Sörensen 1983, Sørensen & Simonsen 1988, Roby et al 1991) and mtDNA as genetic markers (Dodson et al 1991, Birt et al 1995, a set of di-and tetranucleotide microsatellite DNA markers has recently been developed for capelin population discrimination (Røed et al 2003, Gordos et al 2005. The advantage of microsatellite markers compared to other genetic markers is that they are putatively neutral and highly polymorphic, their codominant alleles are easy to score, and they provide more informative results than other markers (cf.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas largescale differentiation has been reported, e.g. separating western and eastern Atlantic stocks (Dodson et al 1991, Birt et al 1995, investigations on smaller geographic scales have led to less conclusive results (Mork & Friis-Sørensen 1983, Sørensen & Simonsen 1988, Dodson et al 1991, Roby et al 1991. The use of microsatellites as genomic DNA markers to analyze the processes of genetic drift and gene flow has increased rapidly over the last years for various species including fish (cf.…”
Section: Introductionmentioning
confidence: 99%